2023
DOI: 10.3389/fnbeh.2023.1226300
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent maternal sleep deprivation aggravates neurobehavioral abnormalities, inflammation, and synaptic function in adult male mice exposed to prenatal inflammation

Abstract: ObjectiveStudies have suggested that prenatal exposure to inflammation increases the risk of neuropsychiatric disorders, including anxiety, depression, and cognitive dysfunction. Because of anatomical and hormonal alterations, pregnant women frequently experience sleep dysfunction, which can enhance the inflammatory response. The aim of this study was to explore the effects of maternal sleep deprivation on prenatal inflammation exposure-induced behavioral phenotypes in offspring and identify the associated mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Recent evidence supports that the expression levels of pro‐inflammatory cytokines and synaptic plasticity–associated proteins are significantly related to cognitive deficits (Zhang, Zhang, Wei et al., 2023 ). Upregulated concentrations of pro‐inflammatory cytokines and downregulated levels of anti‐inflammatory cytokines in the blood are associated with scores of cognitive function in patients with cognitive impairment (Huang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Recent evidence supports that the expression levels of pro‐inflammatory cytokines and synaptic plasticity–associated proteins are significantly related to cognitive deficits (Zhang, Zhang, Wei et al., 2023 ). Upregulated concentrations of pro‐inflammatory cytokines and downregulated levels of anti‐inflammatory cytokines in the blood are associated with scores of cognitive function in patients with cognitive impairment (Huang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 88%
“…Pregnant women must inhale anesthesia in specific situations, which can lead to sleep disorders during the perioperative period. We previously reported that MSD exacerbated the adverse effects of prenatal lipopolysaccharide exposure on cognitive function in offspring mice (Zhang, Zhang, Wei et al., 2023 ). In the present study, offspring mice exposed to isoflurane prenatally and whose mothers were concomitantly subjected to SD (MISO + MSD group) had longer latency and distances to locate the hidden platform in the learning phase of the MWM test, and also had a lower percentage of the total distance and time spent in the target quadrant when compared with offspring mice from the MISO group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations